Peran Kepemimpinan Kiai Dalam Pembentukan Karakter Kewirausahaan Santri Di Pondok Pesantren Mahasiswa Al-Hikam Malang - Zainur Rozikin; Suatmo Pantja Putra (Jurnal Intelek Dan Cendikiawan Nusantara, 2026)
This study aims to analyze the role of kiai leadership in developing the entrepreneurial character of students at Al-Hikam Malang Islamic Boarding School for University Students. This research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observation, and documentation. The research informants consisted of the kiai or Islamic boarding school leader, administrators, mentors, and students involved in entrepreneurial development activities. Data were analyzed through data reduction, data presentation, and conclusion drawing. Data validity was examined through source triangulation, technique triangulation, and member checking. The findings indicate that the kiai plays an important role as both a spiritual and managerial leader in developing students’ entrepreneurial character. The spiritual role is demonstrated through the cultivation of honesty, trustworthiness, responsibility, hard work, modesty, and social benefit. Meanwhile, the managerial role is carried out through direction, motivation, productive activities, task delegation, mentoring, and supervision. The kiai’s exemplary behavior serves as a primary strategy for internalizing entrepreneurial values. In addition, students’ involvement in productive activities and pesantren business units provides contextual learning experiences that support the development of independence, discipline, creativity, innovation, responsibility, and risk-taking. Supporting factors include the kiai’s support, pesantren policies, mentors, facilities, and external partnerships, while inhibiting factors include limited time, differences in students’ interests, and limitations in facilities and mentoring.